2021
DOI: 10.1016/j.eujim.2021.101313
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking history with severe and critical outcomes in COVID-19 patients: A systemic review and meta-analysis

Abstract: Introduction: The highly infectious coronavirus disease 2019 (COVID-19) has now rapidly spread around the world. This meta-analysis was strictly focused on the influence of smoking history on the severe and critical outcomes on people with COVID-19 pneumonia. Methods: A systematic literature search was conducted in eight online databases before 1 February 2021. All studies meeting our selection criteria were included and evaluated. Stata 14.0 software was used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 147 publications
(84 reference statements)
5
44
6
1
Order By: Relevance
“…Although the studies included in our paper (published as of May 25, 2020) reflect the first wave of COVID-19 pandemic, our results (OR 1.59, 95% CI 1.33–1.89, p = 0.001) are consistent with a meta-analyses published after our paper was submitted in September 2020 based on 109 studies from when the pandemic started [ 58 ] to February 2021 (1.55, 95% CI 1.41–1.71) [ 59 ]. Our finding of a higher OR for former than current smokers is also consistent with other analyses published after our paper was submitted [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although the studies included in our paper (published as of May 25, 2020) reflect the first wave of COVID-19 pandemic, our results (OR 1.59, 95% CI 1.33–1.89, p = 0.001) are consistent with a meta-analyses published after our paper was submitted in September 2020 based on 109 studies from when the pandemic started [ 58 ] to February 2021 (1.55, 95% CI 1.41–1.71) [ 59 ]. Our finding of a higher OR for former than current smokers is also consistent with other analyses published after our paper was submitted [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although the majority of evidence has associated smoking with a negative infection prognosis, some studies have reported a non-significant influence of smoking on the severity of COVID-19 (37,44). This is postulated to be related to the angiotensin converting enzyme 2 (ACE2) possible regulatory effect of nicotine, as well to its role in decreasing tumor necrosis factor (TNF) expression in the airways and in serving as an agonist of the cholinergic anti-inflammatory pathway that influences the immune and inflammatory responses (45).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies continue to fuel conflicting results. While most of the studies to date have indicated an association between smoking and increased viral infection susceptibility and worsening of COVID-19 symptoms [24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45], also highlighting the importance of the cumulative pack-year exposure [41], there are several studies that have observed an inverse relationship between smoking and COVID-19 [44,[46][47][48][49][50][51]. In particular, smoking prevalence among patients hospitalized with COVID-19 has been reported to be lower than the smoking prevalence in the general population [46,47,52] and these data were also confirmed in 132 patients who were admitted to our university hospital [53].…”
Section: Discussionmentioning
confidence: 99%